Ginger extract protects metalaxyl-induced histomorphological and histochemical alterations in testes of albino mice - Saber A. Sakr and Somya Y. Shalaby (Journal of Applied Pharmaceutical Science)
Metalaxyl is a benzenoid fungicide used to control soil-borne fungal diseases on fruits, cotton, soybean, ornamental and grasses. Ginger (Zingiber officinale) is example of botanicals which showed many pharmacological effects. The present study investigated the protective effect of ginger extract on metalaxyl-induced testicular abnormalities in mice. Treating animals with metalaxyl caused significant decrease in diameters and germinal epithelial heights of the seminiferous tubules. Histological results revealed that the spermatogenic cells were degenerated and exfoliated in the lumen of the tubules. Inhibition of spermatogenesis was recorded after 6 weeks of treatment with metalaxyl. Histochemical results showed decrease of carbohydrates and total proteins in the testicular tissue. Moreover, metalaxyl led to increase of sperm head abnormalities. Co-administration of aqueous extract of ginger improved the histological as well as the histochemical alterations induced by metalaxyl. This may be attributed to the antioxidant properties of ginger constituents.
Keywords: Metalaxyl, Testis, Ginger, Histology.